Nutritional Status of Under-Five Children and Influential Factors A Control Case Study in the Working Area of Puskesmas Meurah Mulia Kabupaten Aceh Utara - Anwar, Chairanisa (Universitas Ubudiyah Indonesia, 2018)
Factors influencing child nutrition status include nutrition intake, mothers formal education level, motherâs awareness level of nutrition, exclusive breastfeeding, and family income. In some ways, nutrition intake is influenced by mothers characteristic. Also, a mother characteristic participates in determining child nutritional status. Malnutrition becomes a public health problem that will affect the quality of the next generation. Prevalence of malnutrition in Indonesia in 2007 is 5.4%, 4.9% in 2010 and 5.7% in 2013. Nationally, the prevalence of malnutrition has decreased by 5.4% in 2007 to 4.9% in 2010. In Aceh Province, however, the prevalence of malnutrition is still higher than the national rate that is 7.1%. By 2014, data trends on malnutrition in Aceh Province have reported that there were 341 cases of malnutrition, and it has been decreased in 2015 to 307 cases. The purpose of this study was to determine the factors that affect the child nutritional status. This is an observational study with case control research design. Samples were taken by simple random sampling with ratio 1:2 which is 11 cases and 22 controls. The statistical test used was Chi Square Test with 95% confidence level and multivariate analysis of logistic regression with simple method. The results showed that there were two variables that influenced child nutritional status, that are mothers knowledge with p=0,052 and OR=5,950 (95% CI:1,223-28,951) and exclusive breastfeeding variable with p=0,033 and OR=7,600 (95% CI:1,388-41,617). Besides, the result of multivariate analysis showed that the most dominant variable was exclusive breastfeeding with p=0,033 and OR=7,600 (95%CI: 1,388-41,617). A child who was not given exclusive breastfeeding for 6 months will probably suffer malnutrition with risk up to 9,427 times compared to children who was given exclusive breastfeeding for 6 months. It is expected that public health officers could hold a counseling regarding the risk of malnutrition and should build a prevention by helping people to be more aware of the importance of good nutrition for children by giving the children exclusiveÂ breastfeeding.Keywords: motherâs education, family income, exclusive breastfeeding, completeness of immunization, child nutrition status